Risk factors for acquisition of meningococcal carriage in the African meningitis belt. Issue 4 (6th February 2019) - Cooper, Laura V.; Robson, Anna; Trotter, Caroline L.; Aseffa, Abraham; Collard, Jean‐Marc; Daugla, Doumagoum Moto; Diallo, Aldiouma; Hodgson, Abraham; Jusot, Jean‐François; Omotara, Babatunji; Sow, Samba; Hassan‐King, Musa; et al.
Abstract: Objective: To investigate potential risk factors for acquisition in seven countries of the meningitis belt. Methods: Households were followed up every 2 weeks for 2 months, then monthly for a further 4 months. Pharyngeal swabs were collected from all available household members at each visit and questionnaires completed. Risks of acquisition over the whole study period and for each visit were analysed by a series of logistic regressions. Results: Over the course of the study, acquisition was higher in: (i) 5‐to 14‐year olds, as compared with those 30 years or older (OR 3.6, 95% CI 1.4–9.9); (ii) smokers (OR 3.6, 95% CI 0.98–13); and (iii) those exposed to wood smoke at home (OR 2.6 95% CI 1.3–5.6). The risk of acquisition from one visit to the next was higher in those reporting a sore throat during the dry season (OR 3.7, 95% CI 2.0–6.7) and lower in those reporting antibiotic use (OR 0.17, 95% CI 0.03–0.56). Conclusions: Acquisition of meningococcal carriage peaked in school age children. Recent symptoms of sore throat during the dry season, but not during the rainy season, were associated with a higher risk of acquisition. Upper respiratory tract infections may be an important driver of epidemics in the meningitis belt. Abstract : Objectif: Investiguer les facteurs de risque potentiels d'acquisition dans sept pays de la ceinture de la méningite. Méthodes: Des ménages ont été suivis toutes les deux semaines pendant deux mois, puis tous les mois pendant quatre mois. Des prélèvements pharyngés sur écouvillons ont été collectés auprès de tous les membres disponibles du ménage à chaque visite et des questionnaires ont été remplis. Les risques d'acquisition sur l'ensemble de la période d'étude et pour chaque visite ont été analysés par une série de régressions logistiques. Résultats: Au cours de l'étude, l'acquisition a été plus élevée chez: (i) les 5‐14 ans, par rapport à ceux âgés de 30 ans ou plus (OR = 3, 6; IC95%: 1, 4‐9, 9); (ii) les fumeurs (OR = 3, 6; IC95%: 0, 98‐13); et (iii) les personnes exposées à la fumée de bois à la maison (OR = 2, 6; IC95%: 1, 3‐5, 6). Le risque d'acquisition d'une visite à l'autre était plus élevé chez les personnes signalant un mal de gorge pendant la saison sèche (OR = 3, 7; IC95%: 2, 0‐6, 7) et plus faible chez celles signalant une utilisation d'antibiotique (OR = 0, 17; IC95%: 0, 03‐0, 56). Conclusions: L'acquisition du portage du méningocoque a culminé chez les enfants d'âge scolaire. Les symptômes récents de maux de gorge pendant la saison sèche, mais pas pendant la saison des pluies, étaient associés à un risque d'acquisition plus élevé. Les infections des voies respiratoires supérieures pourraient être un facteur important d'épidémies dans la ceinture de la méningite.